Retrospective review of tertiary and neurosyphilis cases in Alberta, 1973–2017. Issue 6 (22nd June 2019) - Landry, Takaaki; Smyczek, Petra; Cooper, Ryan; Gratrix, Jennifer; Bertholet, Lindsay; Read, Ron; Romanowski, Barbara; Singh, Ameeta E
Abstract : Objectives: To review the notification rate and characteristics of tertiary and neurosyphilis cases in Alberta, Canada in the postantibiotic era. Methods: A retrospective review of all neurosyphilis and tertiary syphilis cases reported in Alberta from 1973 to March 2017 was undertaken and cases classified into early neurosyphilis, late neurosyphilis and cardiovascular (CV) syphilis. Variables collected included demographics, sexual partners, HIV status, clinical parameters, symptoms and treatment and distributions were compared between early versus late neurosyphilis and asymptomatic versus symptomatic cases (stratified by early versus late stage). Data were analysed using IBM SPSS Statistics V.19.0. Results: 254 cases were identified; 251 were neurosyphilis and 3 were CV. No cases of gummatous syphilis were reported. Early neurosyphilis accounted for 52.4% (n=133) and 46.1% (n=117) were late neurosyphilis cases; one (0.4%) case with unknown duration. Three outbreaks of infectious syphilis were identified during the study period and a concurrent rise in both early and late neurosyphilis was observed during the outbreak periods. The most common manifestation of symptomatic neurosyphilis was ocular involvement which was more likely in early neurosyphilis. Relative to late neurosyphilis cases, early neurosyphilis cases were more likely to be younger, Caucasian, born in Canada, HIV positive and reporting same sex partners. Conclusions: Our review of tertiary and neurosyphilis cases found that early and late neurosyphilis cases continue to occur in the context of cycling syphilis outbreaks. CV syphilis cases were extremely rare. Ongoing identification of new cases of syphilis and clinical evaluation of cases for complications continues to be important in the context of global resurgence of syphilis.